Peranan Pendidikan, Pekerjaan Ibu Dan Pendapatan Keluarga Terhadap Status Gizi Balita Di Posyandu Rw 24 Dan 08 Wilayah Kerja Puskesmas Nusukan Kota Surakarta - ROZALI, Nur Azikin (2016)
Background: The prevalence of malnutrition in the world still high especiallyin the developement country. The age group most vulnerable to malnutrition are under five years age. One of children death is malnutrition. Parents, especially mother contribute to the nutritional status of children. Mother's education, employment and family income contribute to the nutritional status of children. Objective: To investigate the role of education, maternal employment and family income to the nutritional status of children in Posyandu RW 24 and 08 in Puskesmas Nusukan Working Area of Kota Surakarta. Methods : This study used observational method with cross sectional approach. The sampling technique using simple random sampling. the data of primared were analyzed by chi-square. Result:The mother's education contribute to the nutritional status of children with p-value = 0.001 , maternal employment does not act on the nutritional status of children with p-value = 0.156. the family income does not contribute to the nutritional status of children with p-value = 0.412 Conclusion: Mother's education contribute to the nutritional status of children , mother's employment and family income does not contribute to the nutritional status of children in Posyandu RW 24 and 08 Puskesmas Nusukan working area of Kota Surakarta.